Discussion of an Electronic Examination System in Agricultural HigherEducation - Dövényi-Nagy, Tamás (Acta Agraria Debreceniensis, 2005)
The development of an internet based electronic examination system at the University of Debrecen Centre of Agricultural Sciences, Department of Land Cultivation and Regional Development was enforced by the dynamic increase in the recent years in the number of students participating in classes taught by the department staff. This paper covers the system’s historical background, the usability factors we were focused on during its development, and the experiences of the testing phase. The findings of a questionnaire carried out among our students aimed to clarify the acceptance, expectations and fears of future users.